A necrodane monoterpenoid from Lavandula luisieri essential oil as a cell‐permeable inhibitor of BACE‐1, the β‐secretase in Alzheimer's disease†. (3rd June 2013) - Videira, Rita; Castanheira, Pedro; Grãos, Mário; Salgueiro, Lígia; Faro, Carlos; Cavaleiro, Carlos; Figueiredo, Ana Cristina; Rubiolo, Patrizia
ABSTRACT One of the most important features in Alzheimer's disease is the generation and deposition of neurotoxic β‐amyloid peptide (Aβ). The inhibition of BACE‐1, a key enzyme in Aβ formation, is considered a promising therapeutic alternative for this disease. Natural products from plants have been extensively used as memory enhancers and in dementia therapy, mostly as acetylcholinesterase inhibitors. The low molecular weight and high hydrophobicity of terpenoids are properties that provide a good chance for them to cross cellular membranes and the blood–brain barrier, an essential attribute for BACE‐1 inhibition in vivo. In this study, several essential oils were screened for their inhibitory activity on BACE‐1. One of them, the essential oil from Lavandula luisieri, was signalized as inhibiting the enzyme. Moreover, this oil was tested on the endogenous BACE‐1 in cultured cells, being responsible for a reduction in Aβ production, with no significant toxicity. The essential oil was characterized by a combination of gas chromatography and gas chromatography–mass spectrometry data, showing high contents of oxygen‐containing monoterpenes, mainly necrodane derivatives, which are absent from any other oil. We also describe the bio‐guided fractionation of the oil, as well as tests of the constituents on recombinant BACE‐1 and on a cell line. The main inhibitory activity was assigned to the monoterpenic ketone 2, 3, 4, 4‐tetramethyl‐5‐methylene‐cyclopent‐2‐enone, one of the distinctive components of L. luisieri essential oil. Taken together, these results showed that this essential oil and its components inhibited BACE‐1 activity, both in enzymatic and cellular assays, thus presenting the ability to permeate cell membranes, a novel finding in Alzheimer's drug research. Copyright © 2013 John Wiley & Sons, Ltd.